(untitled) (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
The life and work of Dr. Bhimrao Ambedkar, a prominent Buddhist activist and scholar, have not only left behind a lasting legacy of ideas and access to social justice for the Indian people, but also served as a source of inspiration for citizens across the globe. Regrettably, many young Indonesians, particularly those in the Buddhist community, are unfamiliar with his life story. Consequently, this study seeks to describe the use of a short biographical animation video about Ambedkar’s life in the Religious Studies curriculum at Kertarajasa Buddhist College (STAB Kertarajasa). This short biographical animation video will be employed as a teaching tool to explore topics related to religious diversity around the world and the role of religion as a driving force for social change. Through this case study, the objective of this lesson is to enhance students’ understanding of the various expressions of religion worldwide, with a particular emphasis on Hinduism and Buddhism in India. Additionally, Ambedkar’s powerful vision for achieving social justice provides guidance for prospective teachers in cultivating a critical mindset. The ability to think critically is crucial for aspiring educators, as they must be proactive agents of change. By fostering a critical mindset, these prospective teachers will be better equipped to embrace change and develop innovative and creative solutions. This paper outlines a learning best practice that utilizes a case study of Ambedkar’s life struggle as a means of promoting social equality, religious freedom, and critical education for student-teachers at a Buddhist college through digital storytelling. Key words: Ambedkar, Buddhism, Philosphy of Education, Religious Studies, Religious Dialog, Social Justice.